Health Belief Model Analysis with Perception and Behavior of Mothers of Children Under Five Years Old with Diarrhea - Rosdiana, Rosdiana; Newyearsi, Sri Evi; Yuniar, Dewi (Media Kesehatan Masyarakat Indonesia, 2022)
Diarrhea is still a public health problem in Indonesia. Many children are victim of diarrheal diseases which are easily preventable and treatable. This study aimed to determine the perception and behavior of mothers of children under five years old with diarrhea based on the Health Belief Model (HBM). This research used qualitative with a phenomenological approach and analyzed based on the theory of the Health Belief Model (vulnerabilities, severity, benefits, barriers, cues to action). Collecting data from 12 informants through in-depth interview, observation, and documentation. The results showed that, based on the results of the HBM analysis with 5 indicators, the informants agreed on the susceptibility to diarrhea in children in the area. This is due to unqualified drinking water sources, poor waste management systems, and poor environmental and personal hygiene for each child. The main obstacle for informants is the absence of a strong will and the nature of not caring about the mother's and her children’s living condition and personal hygiene. In conclusion, the informant's perception of diarrheal disease is a harmless disease. The behavior of the informants did not care about living conditions which could cause repeated diarrhea for their children.